Archaeology of the night: life after dark in ancient world - Gonlin, Nancy, editor; Nowell, April, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
A diverse team of experienced scholars used a variety of methods and resources to reconstruct how ancient peoples experienced the night, their views of the dark, their portrayals of the night, and how people in everyday life adapted to the night.--Provided by publisher.
Paleolithic soundscape and the resonance of nighttime / April Nowell -- Classic Maya nights at Copán, Honduras and El Cerén, El Salvador / Nancy Gonlin and Christine C. Dixon -- The night is different: sensescapes and affordances / Kathryn Kamp and John C. Whittaker -- "La luz de aceite es triste": nighttime, community, and memory along the Santa Fe Trail / Minette Church -- Nighttime sky and early urbanism in the high Andes: architecture and ritual in the Southern Lake Titicaca Basin during the Formative and Tiwanaku / Alexei Vranich and Scott C. Smith -- Night in day: contrasting ancient and contemporary Hindu and Maya responses to total solar eclipses / Anthony F. Aveni -- In the sea of night: ancient Polynesia and the dark / Cynthia van Gilder -- Night moon rituals: the effects of darkness and prolonged ritual on Chilean Mapuche / Tom Dillehay -- Where night reigns eternal: darkness and deep time among the ancient Maya / Jeremy D. Coltman -- The Emerald site, Mississippian women, and the moon / Susan M. Alt -- A great secret of the West: transformative aspects of artificial light in New Kingdom Egypt / Meghan E. Strong -- Burning the midnight oil: archaeological experiments with Viking lamps / Erin Halstad McGuire -- Engineering feats and consequences: workers in the night / Rita P. Wright and Zenobie S. Garrett -- Midnight at the oasis: past and present agricultural activities in Oman / Smith Nathan -- All Rome is at my bedside: nightlife in the Roman Empire / Glenn Reed Storey -- Fluid spaces and fluid objects: nocturnal material culture in sub-Saharan Africa with special reference to the Iron Age (CE 200/1900) in southern Africa / Shadreck Chirikure and Abigail Moffett -- The freedom that nighttime brings: privacy and cultural creativity among enslaved peoples at 18th-19th century Bahamian plantations / Jane Eva Baxter.
Keywords: Night -- Social aspects; Night -- Religious aspects; Antiquities, Prehistoric